Hydrogen Bonded Multilayer Films Based on Poly(2‐oxazoline)s and Tannic Acid. Issue 12 (1st October 2014) - Sundaramurthy, Anandhakumar; Vergaelen, Maarten; Maji, Samarendra; Auzély‐Velty, Rachel; Zhang, Zhiyue; De Geest, Bruno G.; Hoogenboom, Richard
<x xml:space="preserve">Abstract</x> In recent years, the layer‐by‐layer (LbL) assembly based on hydrogen bonding interactions is gaining popularity for the preparation of thin film coatings, especially for biomedical purposes, based on the use of neutral, non‐toxic building blocks. The use of tannic acid (TA) as hydrogen bonding donor is especially interesting as it results in LbL films that are stable under physiological conditions. In this work, investigations on the LbL thin film preparation of TA with poly(2‐oxazoline)s with varying hydrophilicity, namely poly(2‐methyl‐2‐oxazoline) (PMeOx), poly(2‐ethyl‐2‐oxazoline) (PEtOx) and poly(2‐n‐propyl‐2‐oxazoline) (PnPropOx), are reported. The LbL assembly process is investigated by quartz crystal microbalance and UV‐vis spectroscopy revealing linear growth of the film thickness. Furthermore, isothermal titration calorimetry demonstrates the LbL assembly of TA, and PMeOx is found to be mostly enthalpy driven while the LbL assembly of TA with PEtOx and PnPropOx is mostly entropy driven. Finally, scanning electron microscopy and ellipsometry demonstrate the formation of smooth thin films for LbL assembly of TA with all three polymers. Such poly(2‐oxazoline) coatings have high potential for use as anti‐biofouling coatings.